The boron partition among coexisting minerals in some igneous and metamorphic rocks - Chawrun, William (My University, 1988)
Separated minerals From 18 different rock samples were available. These came From various locations in the Grenville province. OF these samples, there were 44 minerals which had at least one coexisting mineral phase. These were all analysed For boron by thermal neutron irradiation using the Prompt Gamma Neutron Activation Analysis at McMaster University Nuclear Reactor. There was a preferential boron partition determined For the samples originating From an igneous source, and a numerical value of 0.7 was determined for k-Feldspar/Biotite. There was no Preferential boron partition among the coexisting phases that originated From a metamorphic source. Sphene and Fluorite contained much less boron than other minerals that coexisted with them.
Keywords: mineral; metamorphic rocks; boron partition; geology